Implementing laboratory information management system (LIMS) at National Control Laboratory(NCL), DGDA - Rahman, Sheikh Zamiur (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.